IMPLEMENTASI PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN WOLO KABUPATEN KOLAKA - Yudi Agusman; La Ode Asrun; Putri Yasmin (Journal Publicuho, 2024)
This research aims to understand the implementation of Integrated District Administrative Services (PATEN) in Wolo District, Kolaka Regency. It adopts a qualitative descriptive research method and is conducted within the Wolo District area, Kolaka Regency. The participants in this study consist of community members in Wolo, the District Head of Wolo, the Head of Public Services (Kasi Pelayanan Umum), and personnel involved in integrated administrative services. The data used in this study involves information derived from both primary and secondary sources. The research findings indicate that the implementation of Integrated District Administrative Services (PATEN) in Wolo District, Kolaka Regency, has not yet reached an optimal level. This is evident across four implementation aspects encompassing communication, resources, disposition, and bureaucratic structure. Among these are insufficient socialization efforts among the community, limitations in the number of available service personnel, a lack of friendliness in their demeanour, and frequent delays in the issuance of service documents.